Sandy Soil Improvement Using MICP-Based Urease Enzymatic Acceleration Method Monitored by Real-Time System - Janjit Iamchaturapatr; Keeratikan Piriyakul; Thanate Ketklin; Gemmina Di Emidio; Aruz Petcherdchoo (Advances in Materials Science and Engineering)
This paper aims at monitoring the improvement of sandy soil properties with biocementation through the microbially induced calcite precipitation (MICP) method with reaction accelerations by self-developed soybean urease enzymes. In this study, the concentration of calcium ions (Ca2+ ions as CaCl2) is varied at 50, 100, 250, and 500 mM to determine an optimum shear strength. The self-developed soybean urease enzymes of 20% by volume (v/v) are used to accelerate the MICP reaction to finish within 7 days. Based on real-time monitoring bender element system and direct shear tests, the optimum Ca2+ concentration is found as 250 mM. However, a detrimental effect occurs in case of high concentration of Ca2+ as CaCl2 (500 mM) because of solution acidification from high Cl− concentration. This condition lowers CaCO3 precipitation causing the reduction of biocementation process. At equivalent shear modulus, the biocementation time of MICP-based sand with acceleration by urease enzymes is about 10 times faster than that without. Using spectrophotometer and pH meter, the ammonification rate and the solution pH of biocemented sand with acceleration by urease enzymes for 3 days are found relatively higher than those without urease enzymes for 40 days. The analyses by scanning electron microscopy (SEM) and X-ray diffraction (XRD) confirm not only the occurrence of CaCO3 binding sand particles together but also the improvement of physical strengths of sandy soil samples with the MICP-based urease enzymatic acceleration method. These results introduce an option to accelerate biocemented sandy soil improvement.